The assessment of the students in credit-modular system (Pedagogy of Higher and Secondary Education, 2013)
Antonenko I. I. The assessment of the students in credit-modular system.The features of testing were revealed by computer. The structure tests were substantiated to assess student’s knowledge in a credit-modular training in accordance with the Bologna system. As a result of research the computer method of estimation of knowledges of students is recommended on the base of the program «Assistant».
Keywords: ssessment of the knowledge; the structure of tests; the credit-modular system of training; computer testing; amount of questions